Assessment of the risk of death of Clarias gariepinus and Oreochromis niloticus pulse-exposed to selected agricultural pesticides - Kingsley Chukwuemeka Kanu (Nature Portfolio, 2021)
Abstract Aquatic organisms are often exposed briefly to high pesticide concentration. Survival time model was used to study risk of death in C. gariepinus and O. niloticus fingerlings exposed to 24 mg/L atrazine, 42 mg/l mancozeb, 1 mg/L chlorpyrifos and 0.75 µg/L lambda cyhalothrin for 15, 30, 45 and 60 minutes and continuously for 96 hours. Mortality, time-to-death, weight, length, and condition factor of the fingerlings were recorded. Results obtained showed tilapia was more susceptible than catfish to continuous exposure but not pulse exposure. The survival probability of both species was similar when exposed for 15, 30 and 45 minutes (p > 0.05) but differed after 60 minutes (p < 0.05). Risk of death of catfish exposed briefly to atrazine, mancozeb and chlorpyrifos for 60 minutes was similar to 96 hours continuous exposure, same for tilapia exposed to 1 mg/L chlorpyrifos (p > 0.05). Survival probability of tilapia exposed to chlorpyrifos for 15, 30, 45 and 60 minutes was similar (p > 0.05) and was not influenced by pulse length. Pesticide hazard and risk of death decreased as fish size (weight, length, and condition factor) increased. Pulse toxicity assessment using survival models could make pesticides exposure assessment more realistic by studying factors that can influence the toxicity of pesticides.